The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1167/iovs.14-14602
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight Exposure, Pigmentation, and Incident Age-Related Macular Degeneration

Abstract: Modest associations of eye color, hair color, and HERC2 genotype with any RPAs were found. Genes for AMD did not affect these associations. Eye color phenotype was more strongly associated with outcomes than HERC2 or OCA2 genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 35 publications
0
23
1
1
Order By: Relevance
“…More recently, Klein et al found a modest association of iris color with incidence of early AMD, however there was no association between AMD development and gene markers of iris pigmentation variability (Klein et al, 2014). Another recent study by Schick et al (2015) found no association between iride color and early or late AMD (Schick et al, 2015).…”
Section: Biomarkers Of Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Klein et al found a modest association of iris color with incidence of early AMD, however there was no association between AMD development and gene markers of iris pigmentation variability (Klein et al, 2014). Another recent study by Schick et al (2015) found no association between iride color and early or late AMD (Schick et al, 2015).…”
Section: Biomarkers Of Susceptibilitymentioning
confidence: 99%
“…As AMD is a multi-factorial disease, both genetic and environmental aspects determine development and progression of AMD. Environmental exposure may influence expression of genetic determinants of AMD and genetic susceptibility can worsen effects of environmental exposure (Klein et al, 2014). Both of these factors may also be influenced by epigenetic changes as well (Hutchinson et al, 2014).…”
Section: Biomarkers Of Exposurementioning
confidence: 99%
“…[6–9] This process may explain why excessive sunlight exposure associates with age-related macular degeneration (AMD),[10–12] the third leading cause of worldwide blindness,[13] though other hypotheses have been advanced. [1416]…”
Section: Introductionmentioning
confidence: 99%
“…The phototoxicity-AMD theory is controversially discussed for the past 20 years: some large population-based studies did find an association between environmental light exposure and AMD, while other large population-based failed to support this relationship (Delcourt et al, 2014;Klein et al, 2014;Mainster and Turner, 2009). However, factors of age, gender, genetic factors, smoking, cardiovascular disease, iris colour, even internal antioxidant levels might affect the results (Klein et al, 1992).…”
Section: Discussionmentioning
confidence: 99%